Implementation of hybrid tomatoes as an effort to increase tomato harvest production - Komar Bahtiar; Resti Fajarfika; Hanny Hidayati Nafi'ah (University of Merdeka Malang, 2024)
Tomatoes are a horticultural commodity that is widely cultivated, especially in Bandung Regency. Tomato plants are widely cultivated because they have a fairly high economic value and are in demand by the community because of their many health benefits, among them are vitamin and antioxidant content. Currently, tomato production is declining, so education and assistance are needed to increase the potential for results. The target of this activity is tomato farmers in four sub-districts in Bandung Regency. The purpose of this activity is to increase farmers' knowledge in cultivating hybrid tomatoes at various altitudes. The activity started with counseling, field practice, and evaluation of the results of the activity. As a result of this activity, farmers have additional knowledge in appropriate technology for tomato plants in their respective locations. After the evaluation process, tomato production increased significantly, both in terms of quantity and quality, so it had a positive impact on the economic welfare of farmers.